Responses of Gut Microbial Community Composition and Function of the Freshwater Gastropod Bellamya aeruginosa to Cyanobacterial Bloom - Lyu, Tianying; Zhu, Jinyong; Yang, Xianming; Yang, Wen; Zheng, Zhongming (Frontiers in Microbiology, 2022)
Freshwater gastropods are widely distributed and play an important role in aquatic ecosystems. Symbiotic microorganisms represented by gut microbes can affect the physiological and biochemical activities of their hosts. However, few studies have investigated the response of the gut microbial community of snails to environmental stress. In this study, the dynamics of the gut microbiota of the gastropod Bellamya aeruginosa were tracked to explore their responses in terms of their composition and function to cyanobacterial bloom. Differences in gut microbial community structures during periods of non-cyanobacterial bloom and cyanobacterial bloom were determined. Results showed that the alpha diversity of the gut microbiota exposed to cyanobacterial bloom was lower than that of the gut microbiota exposed to non-cyanobacterial bloom. The main genera differentiating the two periods were Faecalibacterium, Subdoligranulum, Ralstonia, and Pelomonas. Microcystins (MCs) and water temperature (WT) were the primary factors influencing the gut microbial community of B. aeruginosa; between them, the influence of MCs was greater than that of WT. Fourteen pathways (level 2) were notably different between the two periods. The pathways of carbohydrate metabolism, immune system, environmental adaptation, and xenobiotics biodegradation and metabolism in these differential pathways exhibited a strong linear regression relationship with MCs and WT. Changes in the functions of the gut microbiota may help B. aeruginosa meet its immunity and energy needs during cyanobacterial bloom stress. These results provide key information for understanding the response pattern of freshwater snail intestinal flora to cyanobacterial blooms and reveal the underlying environmental adaptation mechanism of gastropods from the perspective of intestinal flora.